Characterization and functional analysis of the BAM gene family in peanut (Arachis hypogaea L.) - Shi, Chaonan; Li, Peilin; Li, Long; Qi, Zhitao; Lu, Tong; Shi, Jinming; Yang, Haodong; Wu, Jin; Guo, Jingyu; Liu, Minghui; Wu, Xiaozong (Frontiers in Plant Science, 2025)
β-Amylase (BAM) is a kind of amylase in plants and microorganisms, which plays an important role in regulating plant growth and development and stress response. This study conducted a genome-wide identification and analysis of the BAM gene family in peanuts, identifying a total of 18 AhBAM genes. The encoded proteins exhibited significant variations in length, molecular weight, and isoelectric points, with primary localization in chloroplasts and nuclei. These genes were unevenly distributed across 10 chromosomes, with chr05 and chr15 each containing three genes. Phylogenetic analysis classified them into four subfamilies, with motif 3 serving as a conserved domain, and segmental duplication identified as the primary mechanism for family expansion. Synteny analysis indicated a closer evolutionary relationship between cultivated peanuts and soybeans. Cis-acting element analysis revealed that AhBAM genes may participate in light signaling, hormone regulation, and stress responses. AhBAM3 emerged as a key node within the protein-protein interaction network, then the GO analysis pinpointed starch metabolism and drought response as the primary functional enrichments for this gene family. Expression profiling showed that AhBAM8 was highly expressed in multiple tissues, whereas most members exhibited no significant response to web blotch disease. This comprehensive analysis provides a holistic view of the potential functions of the AhBAM families in peanuts and lays the foundation for future experimental validation of their roles in enhancing peanut stress resistance and productivity.